Matti Wiberg (ed.), Trying to Make Democracy Work. The Nordic Parliaments and the European Union, Stockholm: The Bank of Sweden Tercentenary Foundation & Gidlunds Forlag. - Munk Christiansen, Peter (Politica, 1998)
-